Family background and home literacy environment as predictors of the early literacy development of children in Wales - findings from the millennium cohort study - Ma, S (2021)
Early literacy and language development plays a vital role in later school success. Home literacy environment has long been recognised as a strong predictor of such development, which is in turn influenced by a child’s family background. We aimed to replicate some of these well-established relationships in a sample of 612 children in Wales, with secondary data obtained from a UK national longitudinal survey, the Millennium Cohort Study. Specifically, we examined the developmental relationships between family background around childbirth (family income, maternal education, maternal literacy/numeracy skills), home literacy environment at age 3 (home tutoring, home literacy practices), precursor English literacy and language skills at age 5 (vocabulary, phonological awareness, print concept), and later English literacy and language outcomes at age 7 (decoding, speaking/listening, reading, writing), controlling for child sex, season of birth, and household single-parent status. Results from a longitudinal structural equation model showed that the effects of family background on literacy and language development were partially mediated by variations in home literacy practices, but not home tutoring; meanwhile, effects of home literacy practices (but not home tutoring) on later outcomes at age 7 were fully mediated by the precursor skills at age 5. Additionally, direct pathways were revealed between family income to early vocabulary at age 5, between maternal education to English writing at age 7, and between maternal literacy/numeracy skills and English reading at age 7. The results suggest that home tutoring may be insufficient to close the attainment gaps from early disparities, and the effects of family background are more salient than previously thought.